CRYOVATE: A Pilot Study of Lung Cancer Cryoactivation in Combination With Immunotherapy in Advanced NSCLC - Antoine Desilets, MD, MSc; Gabryella Pinheiro, PhD; Wiam Belkaid, PhD; Olivier Salko, MD; Julie Malo; Eleyine Zarour, MD; Adeline Jouquan, MSc; Anne-Julie Thibaudeau, MSc; Marc-Antoine Nolin, MSc; John Stagg, PhD; Marie Florescu, MD; Mustapha Tehfe, MD; et al. (JTO Clinical and Research Reports)
Introduction: NSCLC is the leading cause of cancer-related mortality. Although immune-checkpoint inhibitors (ICIs) have improved survival in patients with advanced NSCLC, treatment resistance remains a challenge. Cryoactivation, a technique inducing cell death by cycles of freezing and thawing, has the potential to augment tumor responses when combined with ICIs. Methods: This single-arm phase 1 clinical trial enrolled patients with previously untreated advanced NSCLC and 50% or higher programmed cell death ligand-1 (PD-L1). Patients underwent cryoactivation followed by ICI monotherapy initiated 5 days later. The primary end point was the objective response rate. Co-secondary end points included the safety and feasibility of the procedure and overall survival. Immune cell infiltration by immunohistochemistry was performed on paired pre- and post-treatment samples, with patients dichotomized according to clinical benefit (CB) rate (CB versus no CB [NCB]). Results: Eight patients were enrolled. Two patients achieved a partial response, yielding an objective response rate of 25%. Median progression-free survival and overall survival were 3.8 and 13.0 months, respectively. The cryoactivation procedure was well tolerated, without grade 3 to 4 adverse events. Post-hoc analysis reported a CB rate of 50%. Immunohistochemistry analysis reported a numerical difference in the cluster of differentiation 8–positive (CD8+) T cell infiltration in CB versus NCB in the pre- and post-treatment biopsies (p = 0.09) and an increase in CD8+ T cells in the post-treatment biopsies of CB versus NCB (p = 0.03). Conclusions: Although cryoactivation combined with pembrolizumab was safe and well tolerated in patients with NSCLC, therapeutic benefits were not evident compared with historical cohorts of ICI monotherapy. Correlative analyses validated CD8+ T cell recruitment in patients deriving CB.